GESTIÓN FINANCIERA EN EL GAD PARROQUIAL RICAURTE - Navarrete Arevalo, Maria Jose (2018)
the public section there are immersed sets of organisms through which the state complies with current regulations that are immersed in these administrative bodies. The Autonomous Decentralized Government Paroquial Ricaurte, is an institution founded in the year of 1882 by the dauleño Juan José Guerra, currently directed by Lcdo. Cristhian Lara Guerrero, President of G.A.D. Parroquial Ricaurte.